Penurunan Kepercayaan Masyarakat Indonesia terhadap Institusi Polri Ditinjau dari Psikologi Hukum - Ashara, Zakkialuthfi Chairunnisa; Imanina, Annisa Zahrah; Pramono, Fadia Syiffa; Maryam, Vitanya (Universitas Muhammadiyah Jember, 2023)
Public trust in the Indonesian National Police (Polri) has declined due to the large number of police officers involved in legal cases. This study aims to examine the phenomenon of declining public trust in the Polri institution based on cases occurring in the community. This research is a descriptive qualitative study that employs a systematic literature review method to provide a comprehensive overview of the phenomenon of public trust in the Polri institution. The results indicate that public confidence in the Polri institution was previously considered low due to the large number of cases involving the police. However, the Polri continues to strive to build a positive image to regain public trust by improving its performance, namely, providing protection, guidance, and service to the community.